Pursuit of Stability, Electronic, Lattice Dynamics, and Thermoelectric Properties of Half Heusler Compound TiFeSe - Khatri, Prakash (Api Journal of Science, 2024)
Half-Heusler (HH) compounds are increasingly popular for their use as thermoelectric materials in high-temperature applications. The present work explores the electron and phonon transport properties of TiFeSe compounds to understand their thermoelectric behaviour using Density Functional Theory (DFT), semiclassical Boltzmann transport equation, and Slack's equation. The compound is thermodynamically, dynamically, and mechanically stable, exhibiting non-magnetic semiconductor behaviour with an indirect bandgap of 0.80 eV. The compound has a higher Young's modulus and bulk modulus, indicating better mechanical strength, and also has a high melting point, as calculated from the elastic constants. The lattice thermal conductivity is 24.84 Wm−1K−1 at room temperature and decreases as the temperature increases. The maximum power factor (PF) in the compound for hole doping is 182 μW/cmK², leading to a maximum figure of merit (zT) value of 1.45 at 1200 K. This study shows that the hole-doped TiFeSe compound is a promising candidate for high-temperature power generation in thermoelectric applications.